Alimentación y uso del complemento alimentario en hogares de beneficiarios de la Corporación Educativa Combos (2017)
ABSTRACT: The theme of food and nutrition security, hunger and the meaning of food programs for vulnerable population has been investigated, however, from a qualitative and comprehensive perspective, trying to identify from the perspective of the subjects who experience the phenomenon. Objective: To describe the in-home diet of children who are beneficiaries of the Programa de Atención Integral a la Niñez Trabajadora (PAINIT) of the Corporación Educativa Combos and their perceptions of a nutrition supplement. Materials and Methods: Research was conducted using a qualitative approach, focused ethnography studies, in-depth interviews, and focus groups. Results: Participating families live in situations of hunger and often omit main meals for lack of economic resources. At-home food tends to be traditional, with preference for satiating and inexpensive foods rich in fats and carbohydrates. Outside the home they prefer fast foods due to accesability and affordability. Participants perceive the nutrition supplement as a protector against child hunger, and the food basket as a way to share meals with family on weekends. Conclusions: Impoverished populations prefer foods that are accesible, satiating and economic that allow them to feel full for longer, and tend towards collective or family meals. The services provided by the Corporation were appreciated and valued by the beneficiaries as they have contributed to improving quality of life, family togetherness, and restoration to food security in homes. Key words: malnutrition, food security, poverty, household food insecurity, socio-economic factors, children.